Gamma Radiation Shielding Properties of High-Density Polyethylene - Jemila Mussa Ali; Huda Mousa Hamad (African Journal of Advanced Pure and Applied Sciences, 2025)
In this study, the linear attenuation coefficients LAC, half-value layer HVL, tenth-value layer TVL, and mean free path MFP of high-density polyethylene HDPE samples were measured at 511, 661.7, 1173, 1274, and 1333 keV gamma energies using a NaI(Tl) spectrometer. The gamma-rays were obtained from 22Na, 137Cs, and 60Co sources. The highest value for LAC was 1.41 cm⁻¹ at 511 keV. Conversely, the lowest values for HVL, TVL, and MFP were recorded at the same energy. The results indicated that the linear attenuation coefficient of the HDPE samples was inversely proportional to gamma energies. Conversely, HVL, TVL, and MFP were directly proportional to gamma energies. Consequently, this study concluded that HDPE samples were suitable as shielding material for gamma radiation.